Trousseau's syndrome triggered by an immune checkpoint blockade in a non‐small cell lung cancer patient. Issue 10 (19th July 2018) - Horio, Yuko; Takamatsu, Koutaro; Tamanoi, Daisuke; Sato, Ryo; Saruwatari, Koichi; Ikeda, Tokunori; Nakane, Shunya; Nakajima, Makoto; Saeki, Sho; Ichiyasu, Hidenori; Fujii, Kazuhiko; Tomita, Yusuke
Abstract : PD‐1 blockade therapy activates T cells by blocking the interaction between PD‐1 and PD‐L1 and promotes IFN‐γ and Th1 cytokine production. In turn, IFN‐γ and Th1 cytokines produced by activated T cells promote TF synthesis in monocytes/macrophages, which results in hypercoagulability leading to thrombosis.